2021
DOI: 10.1007/s11612-021-00607-4
|View full text |Cite
|
Sign up to set email alerts
|

Leadership and decision-making under uncertainty

Abstract: ZusammenfassungDieser Artikel der Zeitschrift „Gruppe. Interaktion. Organisation. (GIO)“ gibt einen Überblick über die Herausforderungen des Führens und Entscheiden unter Unsicherheit. Diese Herausforderungen werden am Beispiel des deutschen Corona-Managements illustriert und auf Problemlagen in organisationalen Entscheidungsprozessen bezogen. Der Text verfolgt vorrangig den Anspruch, Dilemmata des Entscheidens in einer Kombination organisationspsychologischer und organisationssoziologischer Perspektiven herau… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 24 publications
2
3
0
Order By: Relevance
“…A first analysis suggests that leaderless groups (i.e., groups in which leader-/followership did not emerge) performed worse in terms of decision quality. This is in line with findings that the emergence of leadership can have an advantageous effect in group movement and group decision making (Boos et al, 2014;Ioannou et al, 2015;Strandburg-Peshkin et al, 2015;Sridhar et al, 2021;von Ameln, 2021). However, as most groups in our study spontaneously exhibited leader-/followership, this result can be only preliminary in nature.…”
Section: Discussionsupporting
confidence: 92%
“…A first analysis suggests that leaderless groups (i.e., groups in which leader-/followership did not emerge) performed worse in terms of decision quality. This is in line with findings that the emergence of leadership can have an advantageous effect in group movement and group decision making (Boos et al, 2014;Ioannou et al, 2015;Strandburg-Peshkin et al, 2015;Sridhar et al, 2021;von Ameln, 2021). However, as most groups in our study spontaneously exhibited leader-/followership, this result can be only preliminary in nature.…”
Section: Discussionsupporting
confidence: 92%
“…Firstly, we observed that organizations focused on acquiring Organizational Environment capabilities, such as advanced technologies and applications, are more adept at navigating all stages of Decision-Making. This aligns with prior studies by [40,65], showcasing how the integration of Organizational Environment and Decision Making can enhance potential contributions to Market Performance. Thus, our results partially support Hypotheses H1, H2, and H3, indicating that Organizational Environment resources significantly influence all stages of Decision-Making, ultimately impacting Market Performance.…”
Section: Discussionsupporting
confidence: 87%
“…With increasing global change (i.e., climate change, social change, geopolitical change), fundamental uncertainties grow; systems elude linear controllability as complexity increases [48]. This reflects that the decision makers we interviewed usually cannot align themselves with only one goal, but often have to meet conflicting expectations and rationalities.…”
mentioning
confidence: 99%
“…However, system trust is also identified as being particularly significant, i.e., trust in the functioning of institutions and rule-and procedure-based decision making, in an integrity of input independent of personal interests and judgments. In acceptance research [48], the management of decisions is also mentioned as an important aspect of making decisions while being uncertain. Von Ameln [48] takes the example of the COVID-19 pandemic to explain the challenges of decision-making processes in uncertain times.…”
mentioning
confidence: 99%
See 1 more Smart Citation